O Biblii brzeskiej – bloczek rocznicowy drugi - Walecki, Wacław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The introduction presents the next stage in the research on the Brest Bible. It is the result of the conference organized in Brest in 2015, which was a continuation of a symposium that was also held in Brest to commemorate the 450th anniversary of the Radziwiłł Bible. The author presented main avenues of research on the Brest treasure and surveyed the themes of papers delivered by the participants. Their articles are included in the present volume of “Tematy i Konteksty”.
On the Brest Bible – the Anniversary Notebook No. 2
Keywords: Biblia brzeska; Biblia Radziwiłłowska; Brześć; Mikołaj Radziwiłł „Czarny”; „Tematy i Konteksty” 4(9) 2014; the Brest Bible; the Radziwiłł Bible; Brest; Mikołaj the Black Radziwiłł; “Tematy i Konteksty” 4 (9) 2014